Efforts to Establish a TB-Free Area: a Case Report - Ilham, Salsabila Nabilla Puspa; Yamin, Ahmad; Mulya, Adelse Prima (Journal of Nursing Care, 2024)
Four pillars of efforts to accelerate TB treatment in Indonesia have not been implemented optimally in Kota Wetan Village, resulting in a high incidence of TB and non-compliance among people with TB. This can hamper the TB elimination program in Kota Wetan Village. Based on the results of the assessment, a nursing diagnosis of TB-related community health deficits was obtained related to the program not addressing all community health problems. This study aims to describe the efforts made to realize a TB-free pioneering area in Kota Wetan Village. The method used was a case report with a nursing process approach. The research sample was the community of RW 15 Kota Wetan Village totalling 695 people. There was an increase in the pretest and posttest scores of health education from an average of 76.25 to 91.25 with a p-value of 0.001 (p<0.050). RW cadres can carry out their duties as PMOs well, sputum examination (BTA) has been carried out for 58 people with suspected TB and household contacts with TB sufferers, and the declaration of TB-free RW has been carried out. The final evaluation found that the nursing problem of community health deficit was partially resolved. These interventions can raise community awareness to actively contribute to the success of activities that are being carried out for the common good so as to reduce the negative stigma of TB disease, increase the discovery of new cases of BTA positive TB, and reduce drug withdrawal rates in TB patients. Widespread community education and multisectoral collaboration are needed to accelerate TB elimination. Keywords: Infectious disease, Public Health Services, Tuberculosis